Bilateral Suprascapular Nerve Injury and Novel Technique of Nerve Transfers for Restoration of External Rotation: Case Report. Issue 4 (19th June 2019) - Abou-Al-Shaar, Hussam; Awad, Al-Wala; Mahan, Mark A
Abstract: BACKGROUND: Complex brachial plexus and peripheral nerve injuries can be challenging to evaluate and treat, especially in the face of novel pathology. OBJECTIVE: To describe the diagnosis of bilateral suprascapular nerve injury, the unique surgical anatomy, and the novel use of a distal nerve transfer to re-establish external rotation. To the best of our knowledge, bilateral suprascapular nerve injury has not previously been reported. METHODS: The authors describe the physical examination and electrodiagnostic and imaging work-up for elucidating complex injury patterns and present a procedure for reinnervating the infraspinatus muscle. RESULTS: A 48-yr-old man presented with profound, right-sided, partial brachial plexus injury incurred 5 mo earlier in a motorcycle accident. Imaging demonstrated atrophy and severe edema within the bilateral supraspinatus and infraspinatus muscles. Needle electromyography depicted no motor units and insertional activities in bilateral infraspinatus muscles, consistent with bilateral suprascapular nerve injury. Along with brachial plexus repair, the patient underwent transfer of a distal branch of the spinal accessory nerve to the inferolateral branch of the suprascapular nerve to the infraspinatus muscle. At 16 mo, he had recovered strong restoration of shoulder external rotation. CONCLUSION: Systematic evaluation can assist in defining complex pathology, particularly with previously unreported types. In this case, predominant injury was inflicted upon the branch innervating the infraspinatus. Highly focal nerve transfers can achieve substantial restoration of external rotation.